The Post-Priestly Pentateuch New Perspectives on its Redactional Development and Theological Profiles - Schmid, Konrad; Giuntoli, Federico (Mohr Siebeck, 2015)
Der nach-priesterliche Pentateuch. Neue Perspektiven auf seine redaktionelle Entwicklung und theologischen Profile.
PublicationDate: 20151113
Keywords: Biblical Exegesis -- Persian Period -- Hellenistic Period -- Redaction Criticism -- Säkularität -- Altes Testament -- Altorientalistik -- Array